Hyaluronidase-based swim-up for semen selection in patients with human papillomavirus semen infection. Issue 1 (21st September 2020) - De Toni, Luca; Cosci, Ilaria; Carosso, Andrea; Barzon, Luisa; Engl, Bruno; Foresta, Carlo; Garolla, Andrea
Abstract: Infection by human papillomavirus (HPV) represents one of the most common sexually transmitted diseases in both men and women worldwide. Recently, the detection of HPV virions in the semen of a large percentage of sexually active men has been associated with detrimental effects on both sperm parameters and on assisted reproductive technologies (ART) treatment outcomes. Conventional semen washing procedure used in ART have proved to be ineffective in removing HPV bound to sperm, requiring the identification of more effective and specific methods. In the present study, we assessed the possible use of hyaluronidase for the detachment of HPV from sperm cell surface. Semen samples from five normozoospermic control subjects (CTRL) were incubated with HPV virus-like particles (HPV-VLP) and treated with hyaluronidase by both a modified swim-up procedure (M-SU) and single-cell approach (SCA). The treatment with hyaluronidase was associated with the complete loss of HPV-VLP signal on sperms by both M-SU and SCA. In addition, semen samples from 12 HPV-positive infertile patients were treated with hyaluronidase 80 IU/mL by M-SU, resulting in the complete loss of HPV-DNA signal from sperm surface. Finally, the possible impact of hyaluronidase treatment on sperm parameters was assessed on both sperms from the five CTRL subjects and on further five oligo-astheno-terato-zoospermic (OAT) patients, both HPV negative. The treatment with hyaluronidase was equally associated with a slight reduction of sperm viability and progressive motility in both CTRL and OAT. In conclusion, the treatment with hyaluronidase removed efficiently and safely HPV virions bound to spermatozoa. Abstract : Summary Sentence The treatment of semen with hyaluronidase associates with total removal of HPV virions bound to spermatozoa, suggesting possible application in assisted reproduction techniques.